2010
DOI: 10.1104/pp.110.162982
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Is Associated with Long-Term Zinc Tolerance in Solanum nigrum

Abstract: Nitric oxide (NO) has been identified as a signal molecule that interplays with reactive oxygen species in response to heavy metal stresses. Roles of NO in regulating cadmium toxicity and iron deficiency have been proposed; however, the function of NO in zinc (Zn) tolerance in plants remains unclear. Here, we investigated NO accumulation and its role in plant Zn tolerance. Zn-induced NO production promoted an increase in reactive oxygen species accumulation in Solanum nigrum roots by modulating the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 58 publications
2
110
0
Order By: Relevance
“…In this work, we showed that copper induced a biphasic increase in NO level that is dependent on NO synthase activity, calcium release, and electron transport in organelles. In this sense, it has been shown that copper and other heavy metals induced NO synthesis in plants and that its synthesis is dependent on an NO synthase-like activity (Tewari et al, 2008;Ramos et al, 2009;Singh et al, 2009;Xiong et al, 2010;Xu et al, 2010). In addition, it was determined that NO synthesis is dependent on calcium release in N. plumbaginifolia and grapevine (Lamotte et al, 2006;Vandelle et al, 2006).…”
Section: Calcium Activates Antioxidant Protein Gene Expression Via Camentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we showed that copper induced a biphasic increase in NO level that is dependent on NO synthase activity, calcium release, and electron transport in organelles. In this sense, it has been shown that copper and other heavy metals induced NO synthesis in plants and that its synthesis is dependent on an NO synthase-like activity (Tewari et al, 2008;Ramos et al, 2009;Singh et al, 2009;Xiong et al, 2010;Xu et al, 2010). In addition, it was determined that NO synthesis is dependent on calcium release in N. plumbaginifolia and grapevine (Lamotte et al, 2006;Vandelle et al, 2006).…”
Section: Calcium Activates Antioxidant Protein Gene Expression Via Camentioning
confidence: 99%
“…On the other hand, heavy metals and metalloids such as copper, zinc, cadmium, aluminum, and arsenic induced NO synthesis in plants that is dependent on an NO synthase-like activity (Tewari et al, 2008;Ramos et al, 2009;Singh et al, 2009;Xiong et al, 2010;Xu et al, 2010). In addition, it was demonstrated that NO synthase is activated by calcium via CaMs in Arabidopsis (Ma et al, 2008).…”
mentioning
confidence: 96%
“…[28][29][30] However, NO can have both protective and cytotoxic effects depending on its concentration and location in the plant cells. 30 Since NO is short-lived and cytotoxic at high concentrations, GSNO could be a proper candidate for bioavailability of NO under physiological and stress conditions.…”
mentioning
confidence: 99%
“…However, an increase in NO was detected in H. verticillata plants exposed to Zn on Day 4, suggesting that excess Zn induced the generation of NO. High Zninduced NO was also found in the terrestrial plants Brassica juncea, Pisum sativum, and Solanum nigrum (Bartha et al 2005, J. Xu et al 2010. Increased NO concentration may be produced by peroxisomes and mitochondria and by the activity of nitrate reductase in plant cells (Xiong et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes like superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT) and guaiacol peroxidase (POD), as well as antioxidant concentrations (for example ascorbic acid) are activated by plants to alleviate oxidative stress (Wójcik et al 2006, Tewari et al 2008, Wang et al 2009). Zn stress can also induce the generation of nitric oxide (NO), an important stress-response hormone (Bartha et al 2005, J. Xu et al 2010. A recent report showed that NO was associated with longterm Zn tolerance in Solanum nigrum (J.…”
Section: Introductionmentioning
confidence: 99%